Reading for Form in Doctrine: Literary Approaches to Przywara’s Analogia Entis - Eikelboom, Lexi (The journal of religion, 2022)
While theology has been in conversation with literary theories for some time, there has been little attention to literary form in theological texts. This leaves us at a disadvantage in understanding how theological texts function in relation to the world in which they are read. This article proceeds through the text Analogia Entis by Erich Przywara from the perspective of three literary approaches to form: aesthetic formalism, new historicism, and new formalism. It suggests that emerging approaches to form gathered together under the heading "new formalism" best explain how a theological text can have disruptive effects beyond the context in which it was first written. Whereas aesthetic formalism abstracts theological texts from their historical contexts so as to render them above critique and new historicism suggests theological texts reproduce the social conditions out of which they arise, a new formalist reading of Przywara shows how we might conceptualize theological texts as opening new possibilities in the contexts in which they are read.